PENGARUH DAYA TARIK DAN PROMOSI WISATA TERHADAP KEPUASAAN PENGUNJUNG KAMPOENG WISATA DI DESA MELIKAN KABUPATEAN KLATEN - Triyono, Joko; Damiasih, Damiasih; Sudiro, Syawal (Kepariwisataan: Jurnal Ilmiah, 2018)
Tourism industry is a sustainable industry, which is supported by the attractiveness and tourist promotion. In Melikan village - Klaten district, there is a tourism industry that has a unique charm in the form of oblique rotation technique. It is also supported by another tourist attraction in the form of courses batik, tempeh, making rambak and traditional toys. In this place also provides facilities such as homestay. The promotion that has been done is through the web, leaflets / flyers and word of mouth. The purpose of this study was to determine the truth of whether there is influence of attraction and promotion of tourism to the satisfaction of visitors. This research method uses a quantitative approach, to know and see the relationship of the variables the study, namely variable attractiveness, promotion of tourism and visitor satisfaction. The research that has been done shows that the attractiveness of positive and significant impact on satisfaction. 84.84% agree. Tourism promotion also affect visitor satisfaction, ie with a percentage of 94.95% agree. While the appeal and promotional simultaneously has significant impact on visitor satisfaction. The second major influence of these variables was 68.8%. While the 31.2% is influenced by other factors, out of these two variables. Keywords: Attractiveness, Tourist Promotion, Satisfation of Visitors, Oblique Rotation Technique